Scaling climate resilient seed systems through SMEs in Eastern and Southern Africa: challenges and opportunities - Shilomboleni, Helena; Recha, John W.M.; Radeny, Maren A.O.; Osumba, Joab J.L. (Informa UK Limited, 2023)
This article examines the potential role of agri-business SMEs in scaling climate resilient seed systems through inclusive business models in Eastern and Southern Africa. Over the last decade, donors and policymakers have coalesced behind a private-sector scaling agenda for Climate Smart Agriculture (CSA) in which small-and-medium enterprises, multinational corporations and financial institutions are recognized for their potential to contribute to the effectiveness and efficiency of aid. This agenda has progressively adopted notions of inclusiveness entailing wider socio-economic empowerment for smallholder farmers and sustainability. Whereas proponents of private sector-scaling of CSA seed systems through inclusive business models make linear assumptions surrounding shared value outcomes and impact at scale for farmers and companies alike, we argue that these dynamics are not always straightforward in practice. For instance, the current focus of CSA seed-related investments towards the formalization and commercialization of seed sectors, does not correspond well to the contextual reality of where ESA farmers source the bulk of their seeds-from diverse channels operating under Farmer-Managed Seed Systems. More careful consideration is needed into the conditions under which inclusive business models could be more compatible with local farming contexts in ways that can support equitable and sustainable transitions at scale.